Taiwan and China: A geostrategic reassessment of U.S. policy. Issue 5 (20th October 2017) - Mitchell, Martin
ABSTRACT: Located offshore of Asia and Mainland China, Taiwan possesses strategic significance because of its location between Japan and The Philippines. Current U.S. policy dates from conditions existent during the Cold War, when China was relatively isolated, economically underdeveloped, and still undergoing the Cultural Revolution, while Taiwan was under martial law and ruled by an authoritarian dictatorship. Taiwan has since evolved into a multiparty, representative democracy while China has transformed itself into a major power, but has retained the one-party authoritarian rule of the Chinese Communist Party. U.S. policy needs readjusting to align with contemporary realities and future trends, which includes finding a balance between its One China policy and allowing the people of Taiwan a significant say in their future. Current American policy fosters a future scenario of poor choices to be made in the context of a crisis instigated at a time of China's choosing.